Socio Economic Suitability of Land Preservation Program in Kuningan Regency - Pramudita, Danang; Dharmawan, Arya Hadi; Barus, Baba (Sodality: Jurnal Sosiologi Pedesaan, 2015)
Economic development in Indonesia since 1980s is dealing with conversion of agricultural land to industry, housing, and other sector in city and its periphery. Land conversion have a great impact to food production rather than the impact from technical problem (drought and pest problem). Government need to preserve agricultural land in order to maintain food production. Thus government made a mandatory approach byissued Law No. 41 year 2009. The aim of this research are to identify an actual socioeconomic characteristics in the area of land preservation program (LP2B) in Kuningan Regency, to identify farmers perception on LP2B and to analyze socioeconomic suitability in the areaof LP2B program. Data were analyzed by descriptive statistics and likert scale. Based on the result, there are nine socioeconomic indicator on land preservation program (LP2B) in Kuningan Regency, namely; land conversion rate, food balance, disparity between farm and non-farm income, agriculture households, agriculture labor, farmers’ groups, spatial planning policies and farmers perceptions. Farmers have a positive perception on LP2B program. Land preservation program (LP2B) priority should be donein Cilimus sub district due to low support of socio economic characteristic. Meanwhile Ciawigebang and Cibingbin sub district become a next priority of preservation.Keyword : farmer’s perception, food security, land conversion, socioeconomic of LP2B